Lessons from "li": a confucian-inspired approach to global bioethics - Jecker, Nancy S. (Journal of medical ethics, 2026)
This paper asks how bioethics navigates, and should navigate, value pluralism in the increasingly global spaces in which bioethics operates. We juxtapose the ethical approaches suggested by East Asian societies, drawing primarily on Confucian ethics, with approaches more prevalent in Western societies, especially North America and Western Europe. Drawing on the Confucian virtue of li (禮) (ritual propriety and decorum), we argue for greater tolerance, respect, epistemic justice, cultural humility and civility. We show how to translate these values into practice using the examples of international bioethics policies governing abortion practice, artificial intelligence governance and climate change. The "Introduction" section raises the question of how to engage in bioethics across borders. The section, "Leading Views of Bioethics are WEIRD" explores how the field of bioethics currently navigates value pluralism. It characterises leading bioethics approaches as WEIRD - Western, educated, industrialised, rich and democratic. The section, "East Asian and Western Views of Personhood" illustrates WEIRD approaches, juxtaposing Eastern and Western accounts of personhood in three cases: social robots, prenatal human life, and nature. The section, "Epistemic Justice and Value Pluralism" argues that bioethics' WEIRDness violates epistemic justice by assigning excess credibility to the West while deflating the credibility of the East. We propose a pluriversal alternative and apply it to bioethics practice by drawing on the Confucian virtue of li. The paper concludes that bioethicists should embrace a pluriversal approach to global value diversity.